Effect of Service Quality on Customer Satisfaction and Organizational Growth - Agwu, M. Edwin; Onwuegbuzie, H. N.; Onasanya, A. Y. (Advances in Social Sciences Research Journal, 2017)
Service quality and customer satisfaction are two very important concepts which plays crucial roles in organizational management and sustenance. The operating environments as well as high levels of competition are forces that are compelling organizational managers to adhere strictly to excellent services in order to achieve high level of customer satisfaction. Expectations in most cases do not match realities in terms of product quality and the services therein and organizational managers lacking behind in this often feel the impacts on their financial bottom line. This paper among others recommends total overhaul of the service qualities in all tiers of marketing management to ensure unmatched satisfaction thereby creating bigger market share.